IMPLEMENTASI KEBIJAKAN PEMANFAATAN PARIWISATA TAMAN NASIONAL BETUNG KERIHUN DAN DANAU SENTARUM (TNBKDS) KALIMANTAN BARAT - Husen, Sadam; Rahmawati, Rita; Hernawan, Denny (JURNAL GOVERNANSI, 2017)
Betung Kerihun National Park and Danau Sentarum (TNBKDS) have tourism potential based on the classification of tourist attraction object (ODTW), if developed and utilized optimally will bring socio-economic impacts for the people around the area of TNBKDS. The purpose of this research is to know the implementation of policy of tourism utilization of TNBKDS in relation of socio-economic impact for society around the area. By using approach of theory of policy implementation model G. Edward III which measure success of policy implementation through 4 variables include; Communication, Resources, Disposition, and Bureaucratic Structure. The method used is descriptive analysis by using quantitative approach. With data analysis techniques using the calculation of Weight Mean Score (WMS). And the analytical unit is divided into 2 sources, namely the implementer of the Central Park TNBKDS based on purposive sampling with the number of samples of 28 employees involved in the field of tourism. And the policy target of the village community Menua Sadap as cultural attractions and the village of Sepandan as a natural tourist attraction TNBKDS with purposive samples each 30 respondents with gender representation, ketokohan, work and so forth. The results of the study are generally based on the assessment of implementing the policy (implementor) is quite good with the acquisition score of 3.33. While the assessment of policy targets based on ODTW classification that is; cultural tourism Menua Sadap obtained a score of 3.49 according to the criteria of interpretation including good category, while the natural attractions Lake Sentarum village Sepandan with a score of 2.60 according to the criteria of interpretation including bad category. Based on the results of the analysis, the difference between the results of the assessment occurs due to communication intensity and bureaucratic structure, and the most fundamental because it is influenced by local culture / culture factors that influence the social, economic and political environment of the policy target itself.policy Implementation, tourism utilization, community of TNBKDS area